5-Substituted 3, 3′, 4′, 7-tetramethoxyflavonoids – A novel class of potent DNA triplex specific binding ligands. (1st April 2022) - Rangel, Vanessa M.; Gu, Landy; Chen, Guanglin; Chen, Qiao-Hong; Xue, Liang
Graphical abstract: Abstract: Herein, we present a class of potent triplex DNA binding ligands derived from the natural product quercetin, which is the first of its kind that has ever been reported in the literature. The binding of 5-substituted quercetin derivatives (3, 3′, 4′, 7-tetramethoxyflavonoids) to triplex and duplex DNA was investigated using several biophysical tools, including thermal denaturation monitored by UV, circular dichroism, differential scanning calorimetry, and isothermal titration calorimetry. Experimental data reveal that several 5-substituted 3, 3′, 4′, 7-tetramethoxyflavonoids have remarkable effects on binding to DNA triple helices, and they do not influence the double-helical DNA structures. A few derivatives such as compounds 5 and 7 have comparable (if not better) binding affinities to neomycin, a well-known DNA triplex binding ligand, under the same conditions. The amino-containing side chains at the 5-position of 3, 3′, 4′, 7-tetramethoxyflavonoids are crucial for the observed binding affinity and specificity.